Enterprise management system - HUANG RIFANG (2018)
The present invention relates to the field of enterprise management, and concretely discloses an enterprise management system. The system comprises: a finance management module, a manpower resource management module, a warehouse management module, a sales management module, a client source management module, a product introduction module, a factory propaganda management module, a fault managementmodule, a device management module, a field management module and a log management module. The enterprise management system allows enterprises to increase income, allows client online repair report tobe accurate and save cost, performs comprehensive grasp of event report of daily work of post outsourcing personnel of the enterprises, assists enterprises managers in improvement of work efficiency,planning unification and formation of system scales, establishes a unified analysis decision platform and optimizes and improves unified management. 本发明涉及企业管理领域，具体公开种企业管理系统，包括：财务管理模块、人力资源管理模块、仓库管理模块、销售管理模块、客户来源管理模块、产品介绍模块、工厂宣传